2022
DOI: 10.1007/s00402-022-04427-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical complications of hip spacers: a systematic review of the literature

Abstract: Introduction Temporary spacers used in the staged revision of a hip prosthetic joint infection (PJI) have been associated with several mechanical complications with very variable reported general complications rates up to 73%. The aim of this systematic review was to assess the mechanical complications associated with hip antibiotic-loaded spacers when treating periprosthetic hip PJI. Methods Through an electronic systematic search of PubMed, articles repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Recent studies suggest avoiding prolonging the interval period to reduce mechanical complications and infection recurrence risks 24 , 25 . In a recent systematic review that analyzed mechanical complications observed during the interval period, the authors reported a weighted mean of 19% for mechanical complications 12 . Spacer dislocation was the most frequent one described in 10.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies suggest avoiding prolonging the interval period to reduce mechanical complications and infection recurrence risks 24 , 25 . In a recent systematic review that analyzed mechanical complications observed during the interval period, the authors reported a weighted mean of 19% for mechanical complications 12 . Spacer dislocation was the most frequent one described in 10.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-spacer and spacer fractures accounted for 3.5% of cases, respectively. Finally, "acetabular complications," such as acetabular osteolysis and pelvic protrusion, were described in 1.2% of cases 12 . In this study, the complication rate reported using the Spaceflex hip G21 spacer is significantly lower than that reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, mechanical complications occur to varying degrees with either type of Spacer. Spacer complication rates reported so far are very variable, reaching up to 73% [ 15 ]. Spacer fracture [ 16 , 17 ] and implant dislocation [ 17 , 18 ], among others, are frequent.…”
Section: Introductionmentioning
confidence: 99%